KMT2C mutation is a diagnostic molecular marker for primary thyroid osteosarcoma: A case report and literature review - Wang, Xinpei; Wang, Qianqian; Su, Peng; Chen, Chunyan; Han, Bo; Liu, Zhiyan (Frontiers in Medicine, 2022)
Primary thyroid osteosarcoma is an extremely rare tumor which is associated with a poor prognosis. In this study, we describe an additional case. A 4.5 × 3.8 cm irregular heterogeneous nodule was examined in the left thyroid gland of a 72-year-old woman. Cytological smears and histopathological specimens showed typical features of osteosarcoma with a neoplastic lesion rich in spindle cells with occasional multinucleated cells and lace-like osteoid matrix. Negative immunoreaction with epithelial markers and positive immunoreaction with SATB2 and low Ki-67 labeling index suggested the diagnosis of osteosarcoma. Multiple KMT2C gene mutations determined by next-generation sequencing further confirmed the diagnosis.